A psychometric investigation of the Bem sex role inventory among Western Cape psychology one students - Betts, John David (Department of Psychology, 2023)
The purpose of this descriptive study was to explore the performance of the Bern Sex Role Inventory (BSRI) (Bern, 1974) amongst South African students. Little information exists about student sex roles in this country. The BSRI is. widely used as a research instrument in South Africa, without investigation of the applicability of the American norms on which it is based to the behaviour of the instrument in South Africa. The primary aims were twofold: firstly, to describe the inventory's behaviour and establish norms for local students; and secondly, to translate the BSRI into the Afrikaans language and establish norms for Afrikaans students. Subjects were two samples of students (N=lSO, n females = 10.9, n males = 41, each). All subjects were classified '·'white", were full time bona fide Psychology One students from the Universities of Cape Town and Stellenbosch. Stratified random samples were drawn from the student populations. Quantitative methods were used to gather the data, namely the BSRI. The BSRI was translated into Afrikaans using backtranslation and decentring methods. A BSRI protocol, a. letter of motivation, and a stamped, addressed envelope were sent to the subjects by mail. Completed protocols were mailed to the researcher. All results were anonymous. Completed protocols were coded, scored, and analysed using statistical software resident on the UCT Sperry-Univac mainframe. The main findings were that the University of Stellenbosch (US) male students were more masculine sex typed than their University of Cape Town (UCT) counterparts. UCT students were found to be more androgynous than US; the BSRI demonstrated high internal reliability, with subscale internal reliability scores demonstrating strong homogeneity of items. The UCT BSRI protocols were factor analysed into two clearly independent dimensions called masculinity and femininity. It was found that the US BSRI protocols did not factor analyse into two clearly independent dimensions. A large factor in the US sample is representative of an androgynous individual in that the factor loaded with positive masculine and feminine BSRI items that Bern (1974) regarded as indicative of androgyny. The implications of the study are that the BSRI masculinity norms developed in the United States are not applicable to South African students. The Afrikaans translation of the BSRI cannot be used to determine sex roles in the same manner as the original BSRI intends. Future research could ·involve the qualitative assessment of sex role, especially in a multi-cultural design.